Mucoceles of the Paranasal Sinuses: MR Imaging with CT Correlation - Van Tassel, Pamela; Lee, Ya-Yen; Jing, Bao-Shan; De Pena, Charles A. (American Journal of Neuroradiology, 1989)
The MR findings in six cases of paranasal sinus mucoceles are described. Two basic MR appearances were encountered: either moderate to marked signal hypointensity in the expanded sinuses on T1- and T2-weighted images (four patients) or moderate to marked signal hyperintensity on T1- and T2-weighted images (two patients). These patterns appear to represent inspissated or hydrated sinus contents, respectively. CT correlation revealed hyperdense mucoceles in the decreased MR signal group and hypo- or isodense mucoceles in the increased MR signal group. Superimposed allergic Aspergillus sinusitis was also present in two patients with hypointense mucoceles on MR.